Clinico-morphological comparison of the mesangiocapillary glomerulonephritis type I and diffuse lupus glomerulonephritis - О. V. Khmara; О. О. Dyadyk; N. F. Yarovaya; Yu. E. Lyakh; V. G. Gurianov (Zaporozhye State Medical University, 2013)
Background. The investigation of the clinical course and morphological diagnostics of glomerulonephritis (GN) are of great importance nowadays due to the large number of patients and their young age. The aim of the study was to identify the correlation between the clinical course and morphological changes in case of mesangiocapillary glomerulonephritis (MCGN) type I and diffuse lupus glomerulonephritis (DLGN) on the basis of complex morphological study of kidney biopsies with the use of statistical methods. Materials and methods. 39 cases with DLGN and 43 cases with MCGN type I were analyzed with routine histological methods and immunohistochemical stains with polyclonal antibodies to IgA, IgG, IgM and complement C3, С1q fractions. In order to establish the link between the clinical morphological data the correlation analysis was used (Spearmen coefficient). Results and discussion. Haematuria severity was higher among the patients with DLGN (p=0,01) than among the patients with MCGN type I; creatinine level, however, was higher among the patients with MCGN (р=0,04); in addition, the diastolic blood pressure level among those patients was also higher (р=0,01) than among the patients with DLGN. Among the patients with DLGN the correlation was established between the levels of proteinuria and the presence of fibrous crescents, severity of dystrophic and necrotic changes in tubular epithelium, as well as IgM deposits at necrotic sites; between the level of haematuria and the level of cellular proliferation and the prevalence of glomerulosclerosis; between the severity of atrophic changes in tubular epithelium. In addition, a correlation was established between the level of creatinine level and presence of subepithelial IgG deposits in glomeruli and IgA deposits in stroma. There was a correlation between the urea levels and the presence of "foamy" cells in stroma, as well as presence of subendothelial IgG deposits in glomeruli, IgG deposits in stroma, presence of subatrophy of tubular epithelium and presence of IgA in glomeruli and IgM deposits at the sites of necrosis. A correlation was also established between the level of systolic blood pressure and the severity of dystrophy and atrophy of tubular epithelium, as well as level of diastolic blood pressure and presence of fibrinoid necrosis, presence of "wire loops", severity of dystrophy of tubular epithelium and presence of subendothelial deposits of IgA in glomeruli, and, finally, with subendothelial IgG in glomeruli. For the patients with MCGN a correlation was established between the level of proteinuria and presence of fibrosis of interstitium; haematuria level and thickening of capillary loops, thickening of capillary basal membrane and presence of IgG deposits in the vessel wall; between the creatinine level and presence of protein masses and cylinders in the lumen of the tubules, stroma infiltration; between the urea level and presence of cellular crescents in glomeruli, presence of IgG and IgM deposits in stroma and subendothelial IgM deposits; between the systolic and diastolic blood pressure level and C1q expression. In conclusion, the study has identified statistically significant differences in the clinical and morphological data of MCGN I type and DLGN course. In addition, correlation was established between the clinical and morphological data in patients with MCGN I type and DLGN, among which there are "active" and "chronic" glomerular, tubule-interstitial changes, which proves the importance of the morphological criteria in prognostication of the disease and pathogenetic treatment.